Technical metaphor and the creation of field - Pueyo, Isabel Gonzàlez (The ESPecialist, 2012)
A considerable piece of research into the construction of knowledge in specialised fields has been carried out within the paradigm of systemic functional linguistics (Wignell, Martin and Eggins, 1987; Eggins, Wignell and Martin, 1987; Halliday, 1987, 1988; Halliday and Martin, 1993). This paper attempts to represent an extension of that body of research into the electronics and telecommunications field. Drawing on White’s distinction between the technological and the scientific, it examines how the discourse of these disciplines construct specialised knowledge through the creation of technicality (White, 1998). With this purpose a representative corpus of data has been analysed. The analysis shows that these disciplines favour elaborately pre-modified nominal groups built from items drawn from the vernacular lexicon and the acronyms derived from these complex groupings. It is suggested that there is an operational and social purpose underlying the communication purpose when these disciplines choose the lexico-grammatical resources in order to construct the phenomenon of their ‘non-commonsense’ ideational domain, and that such lexis provides for a direct connection between the specialist ideational domain and that of vernacular experience.